Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1110/ps.041068605
|View full text |Cite
|
Sign up to set email alerts
|

A novel member of the YchN‐like fold: Solution structure of the hypothetical protein Tm0979 from Thermotoga maritima

Abstract: We report herein the NMR structure of Tm0979, a structural proteomics target from Thermotoga maritima. The Tm0979 fold consists of four ␤/␣ units, which form a central parallel ␤-sheet with strand order 1234. The first three helices pack toward one face of the sheet and the fourth helix packs against the other face. The protein forms a dimer by adjacent parallel packing of the fourth helices sandwiched between the two ␤-sheets. This fold is very interesting from several points of view. First, it represents the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…These proteins have similar subunit folds (Figure 1) but very different sequences (17% identity), quaternary structures (Figure 1), and folding characteristics. Previous NMR and preliminary SEC and light scattering data had indicated that Tm0979 can form a micromolar affinity dimer (23) or a monomer (24) in solution. In order to investigate this further, we analyzed the characteristics of the dimer solution structure by interface analysis programs, DiMoVo (50), PISA (51), and NOXclass (52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These proteins have similar subunit folds (Figure 1) but very different sequences (17% identity), quaternary structures (Figure 1), and folding characteristics. Previous NMR and preliminary SEC and light scattering data had indicated that Tm0979 can form a micromolar affinity dimer (23) or a monomer (24) in solution. In order to investigate this further, we analyzed the characteristics of the dimer solution structure by interface analysis programs, DiMoVo (50), PISA (51), and NOXclass (52).…”
Section: Discussionmentioning
confidence: 99%
“…Protein Expression and Purification. Tm0979 and Mth1491 were prepared using pET15b/BL21(GoldλDE3) expression systems, as described previously (23,28), with the following modifications. For Mth1491, 1 mM ethylenediaminetetraacetic acid (EDTA), 10 mM dithiothreitol (DTT), and 10% (v/v) glycerol were added after elution of the protein from the Ni affinity column to minimize aggregation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, DsrH also fits into the DsrE/F family. Structural information on representatives of the DsrH family of proteins is available through the work of Shin et al on YchN from E. coli, 15 Gaspar et al on Tm0979 from Thermotoga maritima, 16 Christendat et al on MTH1491 from Methanobacterium thermoautotrophicum, 17 and Numata et al on E. coli TusBCD. 18 In contrast to DsrEFH and TusBCD, all others form homooligomers.…”
Section: Introductionmentioning
confidence: 99%
“…This arrangement produces a three-stranded twisted parallel -sheet flanked by helices on both faces. This type of structural arrangement is known as Rossman fold (Gasper et al, 2005). It is shared between diverse families of proteins including dehydrogenases, amidases, nucleotidyl transferases etc (Gasper et al, 2005).…”
Section: Description Of the Structure Of Orf1mentioning
confidence: 99%